Deletion of the Mineralocorticoid Receptor in Myeloid Cells Attenuates Central Nervous System Autoimmunity - Montes-Cobos, Elena; Schweingruber, Nils; Li, Xiao; Fischer, Henrike J.; Reichardt, Holger M.; Lühder, Fred (Frontiers in Immunology, 2017)
Myeloid cells play an important role in the pathogenesis of multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE). Monocytes, macrophages and microglia can develop into two distinct phenotypes, with M1-polarized cells being more related to inflammation and autoimmunity while M2-polarized cells contribute to tissue repair and anti-inflammatory processes. Here we show that deletion of the mineralocorticoid receptor (MR) in bone marrow-derived and peritoneal macrophages caused their polarization towards the M2 phenotype with its distinct gene expression, altered phagocytic and migratory properties, and dampened NO production. After induction of EAE, mice that are selectively devoid of the MR in their myeloid cells (MRlysM mice) presented with diminished clinical symptoms and ameliorated histological hallmarks of neuroinflammation. T cells in peripheral lymphoid organs of these mice produced less pro-inflammatory cytokines while their proliferation and the abundance of regulatory T cells were unaltered. The numbers of inflammatory monocytes and reactive microglia in the CNS were significantly diminished in MRlysM mice and they adopted an M2-polarized phenotype based on their gene expression profile, presumably explaining the ameliorated neuroinflammation. Our results indicate that the MR in myeloid cells plays a critical role for CNS autoimmunity, providing a rational to interfere with diseases such as MS by pharmacologically targeting this receptor.